DAMPAK GEMPA BUMI LOMBOK TAHUN 2018 - Supartoyo; Rahayu Robiana; Merry Christina Natalia; Suryo Hespiantoro (PPSDM Geominerba, 2020)
A series of earthquakes with the mainshock on July 29th, 2018, August 5th, 2018 and August 19th, 2018 occurred in Lombok island. These earthquake has caused 559 fatalities, 1,478 people injured and 185.483 of buildings damaged in the Lombok and Sumbawa island. All type of earthquake hazards occurred namely ground shaking, minor fault surface rupture and collateral hazard such as liquefaction and landslides. Earthquake shaking felt strong in Lombok Utara and Lombok Timur with earthquake intensity scale of VIII MMI (Modified Mercally Intensity). Earthquake on July 29 th , 2018 with magnitude of M 6,4 result rupture zone 218,7762 km2, earthquake on August 5 th, 2018 and onAugust 19th, 2018 with magnitude of M 7,0 result rupture zone 758,5776 km2.